Fly guy presents: Police officers - Arnold, Tedd (New York: Scholastic, 2018)
Fly Guy and Buzz visit a police station and learn about police officers and what they do.
R
b
b
Keywords: Police -- Juvenile literature; Illustrated children's books; Police; JUVENILE NONFICTION -- Careers; JUVENILE NONFICTION -- Law & Crime; JUVENILE NONFICTION -- Reader -- Beginner; Police; Juvenile works; Readers (Publications); Readers (Publications)